Penggunaan Metode Problem Solving Terhadap Efektivitas Belajar Siswa Pada Mata Pelajaran Al-Qur'an Hadist Kelas IX di MTS Negeri 4 Karawang - Nia Nur'aeni; H. Masykur H. Mansyur; H. Abdul Kosim (Peneliti.net, 2021)
He success of al-qur teacher in increasing learning motivation, as well as conducting online learning is the teacher's ability to innovate in designing materials. Problem solving learning method